Confocal fluorescence detected linear dichroism imaging of isolated human amyloid fibrils: role of supercoiling - Steinbach, Gábor; Pomozi, István; Jánosa, Dávid Péter; Makovitzky, József; Garab, Győző (Journal of fluorescence, 2011)
Amyloids are highly organized insoluble protein aggregates that are associated with a large variety of degenerative diseases. In this work, we investigated the anisotropic architecture of isolated human amyloid samples stained with Congo Red. This was performed by fluorescence detected linear dichroism (FDLD) imaging in a laser scanning confocal microscope that was equipped with a differential polarization attachment using high frequency modulation of the polarization state of the laser beam and a demodulation circuit. Two- and three-dimensional FDLD images of amyloids provided information on the orientation of the electric transition dipoles of the intercalated Congo Red molecules with unprecedented precision and spatial resolution. We show that, in accordance with linear dichroism imaging (Jin et al. Proc Natl Acad Sci USA 100:15294, 2003), amyloids exhibit strong anisotropy with preferential orientation of the dye molecules along the fibrils; estimations on the orientation angle, of around 45°, are given using a model calculation which takes into account the helical organization of the filaments and fibrils. Our data also show that FDLD images display large inhomogeneities, high local values with alternating signs and, in some regions, well identifiable µm-sized periodicities. These features of the anisotropic architecture are accounted for by supercoiling of helically organized amyloid fibrils.